Effect of resveratrol on the radiosensitivity of 5‐FU in human breast cancer MCF‐7 cells. Issue 9 (8th May 2019) - Aghamiri, Shahin; Jafarpour, Ali; Zandsalimi, Farshid; Aghemiri, Mehran; Shoja, Mohsen
Abstract: The aim of this study was to assess the efficacy of resveratrol (Res) on radiosensitivity of 5‐fluorouracil (5‐FU) in the spheroid culture of MCF‐7 breast cancer cell line using colony formation examination. Spheroids on day 9 with 300 µm diameters were treated with 20 µM resveratrol and/or 1 µM 5‐FU for one volume doubling time (VDT) (42 hours) and then irradiated with 2 Gy gamma radiation ( 60 Co) in various groups. Then the viability of the cells and clonogenic ability were acquired by blue dye exclusion and colony formation assay, respectively. The population doubling time in the monolayer culture and the VDT of spheroid culture was 22.48  ±  0.23 hours and 42  ±  0.63 hours respectively. None of the drugs and combination of them had any effect on the viability of cells. The combination treatment of 5‐FU+Res+ radiation significantly reduced the colony formation ability of spheroid cells in comparison with each treatment alone. Our results indicated that resveratrol can significantly decrease colony number of breast cancer spheroid cells treated with 5‐FU in combination with gamma‐rays. Thus, resveratrol as a hypoxia‐inducible factor‐1‐alpha inhibitor increased the radiosensitization of breast cancer spheroid cells. Abstract : The aim of this study was to assess the efficacy of resveratrol on radiosensitivity of 5‐fluorouracil in the spheroid culture of MCF‐7 breast cancer cell line using colony formation examination. resveratrol can significantly decrease colony number of breast cancer spheroid cells treated with 5‐fluorouracil in combination with gamma‐rays. Thus, resveratrol as a hypoxia‐inducible factor‐1‐alpha inhibitor increased the radiosensitization of breast cancer spheroid cells.